Environmental change and floods: the long-ignored effects of displacement on mental health - Akram, Sara; Mushtaq, Shama (Frontiers in Public Health, 2024)
Although climate change has received significant global attention, there has been a distinct disregard for the issue of psychological well-being. The elevated floods resulting from climate change have substantial impacts on both physical infrastructure and human well-being. This includes the coerced relocation of individuals from their homes, unemployment, setbacks, and the disruption of communities. The occurrence of significant displacement due to major natural disasters, such as the floods in Pakistan in 2022, is linked to varying degrees of anxiety ranging from moderate to severe.The aim of this research is to perform a comprehensive analysis of the topic by utilizing the available literature. The study aims to ascertain the correlation between floods, caused by environmental shifts, and their influence on mental well-being in Pakistan, specifically focusing on the experiences of susceptible communities. Vulnerable populations, including socioeconomically disadvantaged communities, the elderly, individuals with disabilities, and children, are particularly susceptible to the adverse effects of severe weather conditions. During natural catastrophes, individuals experience elevated levels of psychological, emotional, and physical stress, which subsequently amplifies their vulnerability to these detrimental consequences.